2012
DOI: 10.1021/ef300762z
|View full text |Cite
|
Sign up to set email alerts
|

Metal–Organic Framework Materials for Desulfurization by Adsorption

Abstract: Current European regulations limit the sulfur content of gasoline to 10 ppmw. Such deep desulfurization levels can be achieved by catalytic hydrodesulfurization processes, but they are accompanied by excessive H2 consumption for unwanted side reactions, in particular, for the hydrogenation of olefins. Selective adsorption constitutes an attractive alternative to catalytic desulfurization. The main challenge is to find adsorbents able to remove the sulfur compounds with very high selectivity from a complex mixt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
102
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 123 publications
(104 citation statements)
references
References 51 publications
2
102
0
Order By: Relevance
“…After the doping of BDC‐OH into the Mg II /DOBDC frameworks, the formed materials were made of agglomerated shuttlelike or needle‐type crystals shaped similarly to cauliflowers (Figure 8), in accordance with the previous reports on Mg II /DOBDC 2123. Similarly, after 30 % substitution of BDC‐OH into the Ni II /DOBDC frameworks, the formed materials showed agglomerated needlelike shapes similar to cauliflower shapes (Figure 9) and identical to the reported structure for Ni II /DOBDC 21,24. After 30 % incorporation of BDC‐OH into the Co II /DOBDC framework, the formed materials showed a hexagonal column structure (Figure 10), the same structure as that reported for Co II /DOBDC 21,25,26…”
Section: Resultssupporting
confidence: 89%
“…After the doping of BDC‐OH into the Mg II /DOBDC frameworks, the formed materials were made of agglomerated shuttlelike or needle‐type crystals shaped similarly to cauliflowers (Figure 8), in accordance with the previous reports on Mg II /DOBDC 2123. Similarly, after 30 % substitution of BDC‐OH into the Ni II /DOBDC frameworks, the formed materials showed agglomerated needlelike shapes similar to cauliflower shapes (Figure 9) and identical to the reported structure for Ni II /DOBDC 21,24. After 30 % incorporation of BDC‐OH into the Co II /DOBDC framework, the formed materials showed a hexagonal column structure (Figure 10), the same structure as that reported for Co II /DOBDC 21,25,26…”
Section: Resultssupporting
confidence: 89%
“…low capacity, weak interaction and hardship in regeneration) for contaminant removal in water purification. [40][41][42][43][44][45][46][47][48] During past decades, their applications for water purifications have been widely investigated. Therefore, superior adsorbents with large number of active sites and higher surface areas might be desirable to get a better access to qualified water in a reliable, efficient, convenient and low cost way.…”
Section: Introductionmentioning
confidence: 99%
“…Maes et al have shown that MOFs like the Fe-trimesate MIL-100(Fe) or the Cu-trimesate Cu-BTC are capable of removing the nitrogen or sulfur compounds from a N/S-contaminated fuel. 7,[12][13][14][15][16][17] Using coordinatively unsaturated metal sites increases the heat of adsorption, 18 and therefore the energy input required for desorption of adsorbed molecules. 7,[12][13][14][15][16][17] Using coordinatively unsaturated metal sites increases the heat of adsorption, 18 and therefore the energy input required for desorption of adsorbed molecules.…”
Section: Introductionmentioning
confidence: 99%